2016
DOI: 10.13181/mji.v25i3.1412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiac function tests in Sudanese adult patients with sickle cell trait

Abstract: Background: Cardiac dysfunctions have been recognized as a common complication of sickle cell anaemia (SCA), and together with pulmonary disorder accounts for many deaths in these patients. However, sickle cell traits appear clinically normal, although they have genetic abnormality. The aim of this study was to assess the effect of sickle cell trait on cardiac prognostic markers by measuring high density lipoprotein (HDL-C), low density lipoprotein (LDL-C), cardiac creatine kinase (CK-MB), ultra-sensitive C re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The database search identified 149 citations; as shown in our flowchart ( Figure 1 ), we finally considered 44 articles, 42 of which were full papers [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] plus one thesis [ 53 ] and one abstract [ 54 ] that examined the relationship between HC, MTHFR, and SCD and that were included in our systematic review and meta-analysis. In particular, Table 1 shows the studies that investigated plasma HC in SCD (22 case-control and 2 cohort studies), Table 2 shows the studies that investigated MTHFR TT and cystathionine beta synthase (all case-control), and Table 3 shows the studies that investigated the MTHFR TT genotype in relation to clinical features of SCD (all cohort studies).…”
Section: Resultsmentioning
confidence: 99%
“…The database search identified 149 citations; as shown in our flowchart ( Figure 1 ), we finally considered 44 articles, 42 of which were full papers [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] plus one thesis [ 53 ] and one abstract [ 54 ] that examined the relationship between HC, MTHFR, and SCD and that were included in our systematic review and meta-analysis. In particular, Table 1 shows the studies that investigated plasma HC in SCD (22 case-control and 2 cohort studies), Table 2 shows the studies that investigated MTHFR TT and cystathionine beta synthase (all case-control), and Table 3 shows the studies that investigated the MTHFR TT genotype in relation to clinical features of SCD (all cohort studies).…”
Section: Resultsmentioning
confidence: 99%
“…17 In the highly significant studies-in the article, Abdelsalam, it was reported that tHcy level was found to be insignificantly higher in patients with sickle cell trait when compared to the control group. 18 In thromboembolism and cardiovascular disease, the total homocysteine level was increased in 40% of patients with sickle cell anemia. There was a significant increased mean tHcy level in sickle cell patients by 95% compared to the control group.…”
Section: Discussionmentioning
confidence: 99%